Provocation in the Workplace: A Qualitative Analysis of Published Arbitration Decisions. (September 2019) - Lucero, Margaret A.; Allen, Robert E.
Workplace violence has become a serious concern for managers and unions. This study examined provocation, a precursor to aggression and retaliation, using a grounded theory approach to evaluate a set of published arbitration decisions. The qualitative analysis identified different forms of behavior that provoked targets, as well as the targets' emotional and behavioral responses to the provocation. In addition, analysis of the arbitrators' decision provides a rich source of information on the key factors that can improve management decision making and union responses to these difficult disciplinary issues. Implications of the findings for future research are also discussed.